Exploration of the mechanism and scope of the CuI/DABCO catalysed CS coupling reaction. (15th January 2020) - Thomas, Anns Maria; Sherin, D.R.; Asha, Sujatha; Manojkumar, T.K.; Anilkumar, Gopinathan
Graphical abstract: Abstract: A cost effective and easily available CuI/DABCO catalytic system has been developed for the CS cross-coupling reaction. This method is extremely useful for the thioetherification of aryl and heteroaryl halides, providing excellent yields and good chemoselectivity. We have also explored the mechanism of the reaction using DFT studies.